Students' Civic Online Reasoning: A National Portrait - Breakstone, Joel; Smith, Mark; Wineburg, Sam; Rapaport, Amie; Carle, Jill; Garland, Marshall; Saavedra, Anna (Educational researcher, 2021)
Are today's students able to discern quality information from sham online? In the largest investigation of its kind, we administered an assessment to 3,446 high school students. Equipped with a live internet connection, the students responded to six constructed-response tasks. The students struggled on all of them. Asked to investigate a site claiming to "disseminate factual reports" on climate science, 96% never learned about the organization's ties to the fossil fuel industry. Two thirds were unable to distinguish news stories from ads on a popular website's home page. More than half believed that an anonymously posted Facebook video, shot in Russia, provided "strong evidence" of U.S. voter fraud. Instead of investigating the organization or group behind a site, students were often duped by weak signs of credibility: a website's "look," its top-level domain, the content on its About page, and the sheer quantity of information it provided. The study's sample reflected the demographic profile of high school students in the United States, and a multilevel regression model explored whether scores varied by student characteristics. Findings revealed differences in student abilities by grade level, self-reported grades, locality, socioeconomic status, race, maternal education, and free/reduced-price lunch status. Taken together, these findings reveal an urgent need to prepare students to thrive in a world in which information flows ceaselessly across their screens.